Unexplained regression in Down syndrome: Management of 51 patients in an international patient database. Issue 10 (4th August 2022) - Santoro, Stephanie L.; Baumer, Nicole T.; Cornacchia, Michelle; Franklin, Catherine; Hart, Sarah J.; Haugen, Kelsey; Hojlo, Margaret A.; Horick, Nora; Kishnani, Priya S.; Krell, Kavita; McCormick, Andrew; Milliken, Anna L.; et al.
Abstract: Research to guide clinicians in the management of the devastating regression which can affect adolescents and young adults with Down syndrome is limited. A multi‐site, international, longitudinal cohort of individuals with a clinical diagnosis of Unexplained Regression in Down syndrome (URDS) was collated through seven Down syndrome clinics. Tiered medical evaluation, a 28‐item core symptom list, and interim management are described naturalistically. Improvement—defined by the percentage of baseline function on a Parent‐reported Functional Score, overall improvement in symptoms on a Clinician‐administered Functional Assessment, or report of management type being associated with improvement—was analyzed. Improvement rates using ECT, IVIG, and others were compared. Across seven clinics, 51 patients with URDS had regression at age 17.6 years, on average, and showed an average 14.1 out of 28 symptoms. Longitudinal improvement in function was achieved in many patients and the medical management, types of treatment, and their impact on function are described. Management with intravenous immunoglobulin (IVIG) was significantly associated with higher rate of improvement in symptoms at the next visit ( p  = 0.001). Our longitudinal data demonstrates that URDS is treatable, with various forms of clinical management and has a variable course. The data suggests that IVIG may be an effective treatment in some individuals. Our description of the management approaches used in this cohort lays the groundwork for future research, such as development of standardized objective outcome measure and creation of a clinical practice guideline for URDS.